Varieties of conservatism in America - Berkowitz, Peter, 1959- (Hoover Institution Press publication ;, 2004)
The essays in this volume demonstrate that the debate among conservatives about which principles and practices are most urgently in need of protection is also a debate with that larger liberalism that undergirds the American constitutional order. The essays suggest as well that this larger liberalism, with its bedrock devotion to individual liberty and equality before the law, serves as the common ground on which the contending camps within conservatism - and indeed conservatives in their contentions with progressives - can come together, debate civilly, and discover ways to advance the public good.